Evaluating the expression of HMGCR in HER2 negative and HER2 positive breast cancer - Drahman, Rosmaizan (2022)
3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) is the rate-limiting enzyme in cholesterol biosynthesis pathway that has been associated with cancer development. Although the connection between HMGCR and HER2 has been established, the function of HMGCR in the advanced progression of HER2 positive breast cancer and anti HER2 therapy resistance remains unknown. The purpose of this research is to study the expression of HMGCR in HER2 positive and HER2 negative breast cancer and to determine the association between HMGCR expression and clinicopathological characteristics of breast cancer patients. Breast cancer cell lines MDA-MB-453 and MDA-MB-361 (HER2 positive), MDA-MB-231 and MCF-7 (HER2 negative) were cultured in DMEM media supplemented with 4% FBS and 1% antibiotic. When the cells reached confluence, they were subcultured in Petri dishes for protein extraction and western blotting. In addition, the levels of HMGCR mRNA were determined by qPCR analysis on FFPE (formalin fixed paraffin embedded) breast cancer tissues with IHC scores of HER2 0, HER2 1+, HER2 2+ and HER2 3+. Moreover, HMGCR immunohistochemistry (IHC) staining was conducted on FFPE HER2 positive and HER2 negative breast cancer tissues. In comparison to other breast cancer cell lines, the HER2 positive cell line MDA-MB-453 had a high level of basal HMGCR protein (p=0.011). Furthermore, HMGCR mRNA expression was much greater in HER2 IHC 3+ breast cancer samples than in other HER2 breast cancer subtypes, but this difference was not statistically significant (p=0.118). According to the IHC study, the percentage of HER2 IHC 3+ samples with high HMGCR protein expression was 88.9 % (32 out of 36 cases), which was considerably greater than the percentage of HER2 IHC 0 & 1+ samples with high HMGCR protein expression of 69.4 % (25 out of 36 cases) (p=0.042). However, the association analysis revealed that the majority of breast cancer cases with high HMGCR expression were among samples with HER2 positivity, a larger tumour size (> 2cm), high scores (Score 2 and Score 3) on tumour grade parameters such as nuclear pleomorphism, tubular formation, and mitotic count, a higher tumour grade (Grade 2 and Grade 3), ER positivity, PR negativity, and the presence of lymph node involvement. The correlations, however, were not statistically significant. Our results contribute to the existing body of knowledge on the link between HMGCR expression and HER2 positive breast cancer. Further research should be conducted to determine the molecular connections between HMGCR and HER2 positive breast cancer in relation to tumour development and resistance to anti-HER2 treatment in HER2 positive breast cancer.